Peramalan Permintaan Toza Juice Strawberry Sebagai Dasar Penentuan Kebutuhan Persediaan Bahan Baku - Sri Mulyati; Nurul Fadilah; Khaerul Saleh (JURNAL AGRIBISNIS TERPADU, 2019)
Fruit juice is one of the favorite soft drink products in Indonesia. PT. Amanah Prima Indonesia is an agroindustry company that produces the fruit juice RTD for the HORECA market. In the company’s activities, the company will not be separated from a plan. One of the planning activities is forecast demand. The results of product demand forecast can assist in the decisions making to determine the amount of raw material inventory needs. The purpose of the research are: 1) to find out the forecast method used by the company, 2) to analyze the best demand forecast method, and 3) to analyze the optimal amount of the raw material inventory requirements based on the best forecast method results. This research used product sales data in the period of May 2016-April 2018. Demand forecast analysis used the ARIMA method and Exponential Smoothing method. Then inventory analysis used the Min-max Stock method. The result of this research shows that the forecasting system used by the company is currently unrealistic because it has big significant of difference with the actual data. The best time series model of forecast analysis acquires ARIMA model with value of MSE was smaller than DES (Holt) model. Analysis of the raw material inventory requirements with Min-Max Stock results obtain supplies the raw material of strawberry puree is 1688 kilograms, with safety stock of 106 kilograms puree, minimum stock of 830 kilograms puree, maximum stock of 1447 kilograms puree, and reorder point for the next purchase of strawberry as much as 562 kilograms.